2019
DOI: 10.1021/acscatal.9b01585
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Coupling of Methane (OCM) by SiO2-Supported Tungsten Oxide Catalysts Promoted with Mn and Na

Abstract: The literature for the oxidative coupling of methane (OCM) on supported Mn/Na 2 WO 4 /SiO 2 catalysts is systematically and critically reviewed. The influence of the precursors, starting SiO 2 support crystallinity, synthesis method, calcination temperature, and OCM reaction conditions on the catalyst structure is examined. The supported Mn/Na 2 WO 4 /SiO 2 catalyst system is found to be dynamic with the catalyst structure quite dependent on the set of variables. Although almost all of the reported studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
153
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 104 publications
(325 reference statements)
9
153
3
Order By: Relevance
“…It can be observed that almost all these catalysts fall in the 2 nd quadrant, being characterized by above-median rankings. This is in agreement with the fact that many of the top-performing catalysts reported in literature belong to this catalyst family 61 . However, promoted NaMnW/SiO2 catalysts have proven to be thermally unstable and, thus, prone to deactivation 55 and alternatives for adiabatic operation shall thus be explored.…”
Section: Catalyst Ranking In Isothermal Vs Adiabatic Operationsupporting
confidence: 90%
See 1 more Smart Citation
“…It can be observed that almost all these catalysts fall in the 2 nd quadrant, being characterized by above-median rankings. This is in agreement with the fact that many of the top-performing catalysts reported in literature belong to this catalyst family 61 . However, promoted NaMnW/SiO2 catalysts have proven to be thermally unstable and, thus, prone to deactivation 55 and alternatives for adiabatic operation shall thus be explored.…”
Section: Catalyst Ranking In Isothermal Vs Adiabatic Operationsupporting
confidence: 90%
“…However, promoted NaMnW/SiO2 catalysts have proven to be thermally unstable and, thus, prone to deactivation 55 and alternatives for adiabatic operation shall thus be explored. Therefore, even though not specifically addressed in the present work, the screening and selection procedure should not disregard issues such as phase transformation, thermal stability and potential deactivation, measured via, for instance, operando characterization 61 . If catalysts such as the ones in the 1 st quadrant would prove to be more suitable than nd quadrant catalysts in this respect, the former would be of higher interest.…”
Section: Catalyst Ranking In Isothermal Vs Adiabatic Operationmentioning
confidence: 99%
“…Among them, the Na-Mn-W/SiO 2 is generally accepted to be one of the most promising catalyst materials showing high catalytic performance (> 20 % yield) and long-term stability [15][16][17] . Numerous studies and reviews [18][19][20] have focused on investigating the nature of active phases/species as well as on determining the optimal catalyst composition, preferred preparation method and the role of catalyst promoters. It should be noted though that there is still much debate regarding the phases/species of the Na-Mn-W/SiO 2 catalyst including two main theories regarding the nature of active site(s).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative coupling of methane (OCM) reactions, in which methane (CH 4 ) is partially oxidized to C 2 hydrocarbons such as ethane (C 2 H 6 ) and ethylene (C 2 H 4 ) in a single step, represent a long‐standing challenge in the field of catalysis [29–31] . Successful OCM is difficult because the C 2 hydrocarbon products are more reactive than CH 4 and readily undergo nonselective oxidation to CO x [32–34] .…”
Section: Introductionmentioning
confidence: 99%